The influence of older people on the formation of the spiritual environment in Uzbek families. - Mamayusupova Iroda Khamidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article highlights the issues of family and family relations. The features of the specific influence of experience, upbringing and advice on the organization of family relations among representatives of the older generation are described. It is shown that if the family is healthy and strong, then peace and harmony can be achieved in the neighborhood, therefore only with a strong neighborhood peace and stability will reign in the state, family well-being is the basis of national well-being, and the elderly have their place in the formation of the spiritual and moral environment interpersonal relations in Uzbek families. They are the keepers of the rich spiritual and moral values ​​created by their ancestors, heirs and creators of new conditions, they are considered grateful teachers who educate the younger generation. The influence of older people on the formation of the spiritual and moral environment in the interpersonal relations of Uzbek families is analyzed.